THE ROLE OF YOUTH IN MODERATE ISLAMIC PUBLICATION EFFORT THROUGH THE LITERATURE MOVEMENT - Rizky Saputra (Universitas Islam Balitar, 2021)
Literacy has an important role in the life of the nation, state and religion. Besides being able to foster a broad understanding in each individual, literacy can be an effective tool to prevent disintegration or division between individuals in a pluralistic society. Through the literacy movement, religious moderation efforts, especially for Muslims in Indonesia today, will be much easier to implement and distribute their ideas. Reflecting on the recent situation, where Muslims often reap negative justifications for every act of violence committed by a Muslim who lacks an understanding of literacy related to the character and substance of Islamic teachings. Publication steps against moderate Islamic thought is an effective solution. Besides being able to become the best instrument of unity for the benefit of Muslims, moderate Islamic publications can be used as a step for deradicalization and optimizing the prevention of extremist ideas, acts of terror, and the like. Thus, the integrity of the nation and state as well as ukhuwah Islamiyah can be well maintained in Indonesia.